NbCl5 a multifunctional reagent for the synthesis of new halogenated aminoquinoline compounds through innovative one-pot reaction and the acidochromism effect - dos Santos, Giovanny Carvalho [UNESP]; Moreno, Vitor Fernandes [UNESP]; Oshiro, Paula Beatriz [UNESP]; da Silva-Filho, Luiz Carlos [UNESP] (Elsevier, 2018)
This paper describes an original one-pot way to synthesize nine new halogenated aminoquinoline derivatives using reactions conducted by niobium pentachloride. Subsequently, we describe an efficient and selective reduction reaction of nitroquinolines using niobium pentachloride and zinc, producing important compounds in the organic synthesis. The results showed that it is an important tool to synthesize these compounds, besides being time- and resources-saving and generating good yields. A quick study of acidochromism was performed.
Keywords: Aminoquinoline derivatives; Niobium pentachloride; One-pot reactions; Selective reduction reactions